Self-disclosure of HIV serostatus in recently diagnosed patients with HIV in South Africa (2004)
Failure of people living with HIV/AIDS to disclose their HIV serostatus can place their sexual partners at risk. The current study examined HIV serostatus disclosure and its relationship to risky sexual behaviours in 69 sexually active, heterosexual, married (62%) or cohabiting (38%) patients recently diagnosed as HIV positive. Results show that 78% had not disclosed their HIV serostatus to their sexual partners and 46% had no knowledge of their sexual partner's serostatus. Compared to those who disclosed their serostatus, those who did not disclose were more likely to be male (X2 = 7.02, p = 0.00), to have not used a condom during their last sexual encounter (X2 = 29.64, p = 0.000), to have used alcohol heavily before sex (X2= 6.79, p = 0.00), to have multiple sexual partners (t = 3.01, p = 0.05), and to have engaged more frequently in sexual intercourse in the six months preceding the study (t = 8.21, p = 0.00). Logistic regression analysis show that being in a married relationship (OR = 0.86, 95% CI = 0.65,1.15), being male (OR = 1.48, 95% CI = 0.24,1.99), having more than two multiple partners (OR = 2.03, 95% CI = 1.11, 3.68) and non-use of condom at last sex (OR = 1.53, 95% CI = 0.83, 1.88) were significantly associated with non-disclosure of HIV serostatus. Preventive strategies among HIV- positive patients should place emphasis on the management of self-disclosure and its importance in safe sexual behaviour.